96 Impact and Feasibility of a Pediatric Social Determinants of Health Questionnaire: A Pilot Mixed-Methods Study. (21st October 2022) - Carwana, Matthew; Ricci, Taylor; DiCicco, Alesia; Ponton, Ethan; Duffy, Damian; Courtemanche, Rebecca; Lau, William; Singh, Tanjot; Loock, Christine
Abstract: Background: Social determinants of health (SDoH)—which are factors such as socioeconomic status (SES), access to transportation, food and housing security, disability and social supports—have been shown to influence up to 50% of health in patients. The project team developed a SDoH Questionnaire which evolved into what is now referred to as BEARS (Barriers to Care, Economic Factors, Adversity, Resiliency, Social Capital). Part of the BEARS Questionnaire includes an optional section for inquiring about Adverse Childhood Experiences (ACEs). Objectives: The primary purpose of this study was to evaluate the impact and feasibility of the BEARS Questionnaire. Additional objectives were to assess the utility and functionality of the BEARS Questionnaire as a social history-taking tool, including the cumulative ACEs questions, and obtain suggestions for improvement of the tool. Design/Methods: This was a mixed methods pilot study that consisted of quantitative surveys and qualitative structured interviews with clinicians who had experience using the BEARS Questionnaire. Descriptive statistics were performed on all survey results. Thematic analysis was performed on clinician interviews with recurrent themes being identified through iterative analysis and tagged quotations. Results: 15 clinicians completed the quantitative survey and five took part in a qualitative interview. Study participants included surgeons, pediatricians, speech language pathologists, social workers and nurse clinicians. The BEARS Questionnaire changed clinician practice by increasing the frequency and breadth of social screening in their patients and optimizing care to fit their patients' social context. Participants described the BEARS as an effective screening tool for SDoH and ACEs that was feasible to implement into their clinic workflow. Three themes emerged from our interviews: (1) Thorough social history taking highlights family resiliency and improves clinician-patient rapport, (2) Screening for ACEs is acceptable and feasible in a safe clinical environment, and (3) Social screening is feasible in a busy clinical environment and there is room for improvement. Conclusion: This study highlights the importance of social screening in pediatric patients and their families, and how using a social screening tool allows providers to tailor care for a patients' social context. The BEARS Questionnaire is feasible to implement within the context of a busy clinic. Finally, despite being a sensitive topic, an ACEs questionnaire can be incorporated when done in a trauma-informed way, and in the context of a longitudinal therapeutic relationship.